High‐Speed Solar Wind Streams in 2007–2008: Turning on the Russell‐McPherron Effect. Issue 11 (21st November 2019) - Munteanu, C.; Hamada, A.; Mursula, K.
Abstract: Two sequences of five high‐speed solar wind stream/corotating interaction region (HSS/CIR) events were observed at 1 AU in December 2007–2008. These two HSS/CIR sequences had opposite magnetic polarities, and they originated from two persistent low‐latitude coronal holes with corresponding polarities. Each HSS/CIR event triggered a geomagnetic storm and strong high‐latitude activity. We follow the evolution of the properties and geomagnetic effects of the two sequences and find that the sequence with negative interplanetary magnetic field polarity (toward sector) develops systematically a more negative Bz(GSM) component and becomes relatively more geoeffective when moving from winter solstice in 2007 to spring equinox in 2008. On the other hand, the sequence with positive polarity (away sector) develops systematically a less negative Bz(GSM) component and becomes relatively less geoeffective. These changes allow the first detailed monitoring of the turning on of the Russell‐McPherron effect when moving from solstice to equinox and the development of the related changes in high‐latitude geomagnetic activity and geomagnetic storms. Key Points: We study two sequences of stable high‐speed streams with opposite polarities in 2007–2008, locate their sources and follow their effects IMF Bz(GSM)‐Bz(GSE) difference decreases (increases) systematically in the negative (positive) polarity sequence from solstice to equinox We quantify the effect of this turning on of the Russell‐McPherron mechanism to high‐latitude geomagnetic activity and geomagnetic storms